(untitled) (Nomico, 2025)
High stock price volatility can trigger market instability and increase the risk of investor losses. To manage such fluctuations, the Indonesia Stock Exchange (IDX) implements the Auto Rejection Upper and Lower (ARA–ARB) policy as a daily price movement limit. In the context of the Islamic capital market, it is essential to examine whether this policy aligns with Islamic economic law and the objectives of maqāṣid al-sharī‘ah, particularly in promoting justice (‘adl), avoiding excessive uncertainty (gharar), and ensuring public welfare (maslahah). This study aims to analyze the conformity of the ARA–ARB mechanism with these principles. The research employs a normative-doctrinal approach through document analysis of regulatory texts, including IDX Board of Directors’ Decrees, OJK regulations, and DSN-MUI Fatwas, complemented by literature review and synthesis of empirical studies from 2020 to 2023. The findings indicate that, from a normative perspective, the ARA–ARB policy is consistent with maqāṣid al-sharī‘ah as it helps reduce extreme volatility, minimizes gharar, ensures fairness and transparency, and is free from elements of riba. Empirically, ARA–ARB provides positive signals toward abnormal returns under certain conditions, although often followed by a short-term decline in trading volume. This implies a trade-off between price stability and market liquidity. The study recommends regular sharia compliance evaluations, enhanced involvement of the Sharia Supervisory Board, and improved transparency and investor literacy to ensure that the implementation of ARA–ARB remains consistent with Islamic principles while supporting a stable and resilient capital market in Indonesia.